(untitled) (Research, Society and Development, 2022)
The new paradigm of Industry 4.0 implies the use of digital tools (DT) for activities related to the operations of companies that obtain goods or services through Management systems such as Quality (QMS) and Sustainability (SGS). These many companies do not operate with the speed and effectiveness necessary for increasingly demanding markets due to ignorance or deficient use of these tools for effective information on management systems. The objective of this work was to determine the relationship between the study variables, for which dimensions and indicators show the knowledge and good use of DT, and its results in the management systems indicated. Based on the empirical research and its results, a model is proposed for the making of relevant decisions by companies that are in similar cases.